Planting Patterns Affect the Differences in Growth and Its Responses to Nitrogen Forms and Levels Between Three Invasive and Their Respective Related Native Species - Wei-Wei Feng; Kai Huang; Si-Miao Sun; Jian-Kun Sun; Ming Guan; Fa-Zhao Qi; Ming-Chao Liu; Bo Qu; Yu-Long Feng (Plants)
Global changes, such as atmospheric nitrogen deposition, can facilitate alien plant invasions, which are often attributed to the increase in soil nitrogen availability. However, few studies have considered the effects of global change-driven alterations in soil nitrogen forms, especially under conditions with interspecific competition. In this study, we first determined the differences in growth, biomass allocation, and photosynthesis under different nitrogen forms and addition levels between three noxious invasive species (Xanthium strumarium, Ambrosia trifida, and Bidens frondosa) and their respective related natives grown with and without interspecific competition and then assessed the interspecific difference in nitrogen form preference using the 15N labeling technique. Interspecific competition significantly decreased the positive responses of growth to nitrogen addition for all three natives, while increasing the responses for all three invaders, particularly under nitrate addition. When grown in competition, all invaders showed significant growth advantages over their related natives in most cases, and responded more positively to the addition of nitrate relative to ammonium, while the natives responded more positively to ammonium addition. These findings indicate that the invaders prefer nitrate, while the natives prefer ammonium. Consistently, the growth advantages are more pronounced for the invaders under nitrate relative to ammonium addition, indicating that nitrate-rich habitats may be more vulnerable to the invaders. When grown in monoculture, however, the growth advantage of the invaders became smaller or even disappeared. Nitrogen form preference also disappeared in Siegesbeckia glabrescens (native) and Bidens frondosa (invasive). Interestingly, the native plant Xanthium sibiricum showed significantly higher total biomass than its invasive congener under ammonium addition in both mixed and monoculture conditions. Our 15N labeling experiment showed that all six species preferred nitrate over ammonium, although this was not significant for two natives (S. glabrescens and X. sibiricum), which is not completely consistent with the results from our nitrogen addition experiment. Our results indicate that global change-driven alterations in soil nitrogen forms, particularly the shift from ammonium to nitrate, may facilitate alien plant invasions. Planting patterns significantly affect the responses of invasive and native species to nitrogen forms and addition levels, with mixed-culture experiments providing better insights into the invasiveness of alien species.